Basic Principle and Step-by-Step Procedure of Abdominal Hysterectomy: Part 2 - Konishi, Ikuo (The Surgery Journal, 2019)
Abdominal hysterectomy is the ultimate standard operation among various gynecologic surgeries. However, the actual procedure for a patient varies substantially according to the morphological changes of the uterus and adnexa. Therefore, it is important to assess the deviation from standard and the difficulties in the procedure and to plan the modification of the operation at the preoperative conference. In this chapter, a standard step-by-step procedure for abdominal hysterectomy is described.
Keywords: abdominal hysterectomy; standard procedure; uterine fibroids; MRI